Inovação sustentável nas cadeias de suprimentos: proposta de modelo orientado ao mercado consumidor regional - Barreto, Lucas Silva (2022)
Historically, many organizations have obtained significant profits at the expense of serious socio-environmental impacts. However, scarcity of resources and damage to institutional image have led organizations to rethink their business models. Stakeholders have been demanding practices of sustainable innovation in supply chains (SISC), through the introduction of new or improved products, production processes, practices, or business models that reconcile economic, social, and environmental results. Nevertheless, the literature presents some obstacles to the successful adoption of sustainable practices in supply chains: short-term managerial approaches restricted to profit maximization; studies limited to the analysis of focal organizations or dyadic relationships, which disregard the consumer as the primary stakeholder; few studies based on the theory of dynamic capabilities; and the proposition of uniform global sustainability guidelines, which may be misaligned with local and regional needs. Regarding behavioral aspects, it is argued that understanding human behavior may offer subsidies for a transition to sustainable development, even more efficient than technological innovation. Within the scope of consumer behavior, the concept of perceived effectiveness may be important for the adoption of sustainable innovations and refers to the way consumers judge that their attitudes are capable of affecting socio-environmental problems. In this sense, the general objective of this thesis is to propose a model of sustainable innovation in supply chains oriented to the consumer market, considering the organizational dynamic capabilities, the perceived effectiveness and the regional impact. The thesis is divided into two studies: the first seeks to analyze, from the perspective of the consumer market, the relationship between perceived effectiveness on a global and regional scale, the perception of sustainable innovation practices and the consumer's intention to purchase; and the second intends to investigate, from the organizational perspective, the relationship between the dynamic capabilities of market perception and innovation, sustainable innovation in supply chains and market performance. Based on a survey with 253 consumers and 137 specialists, with data analyzed by means of structural equation modeling, we identified that: (1) perceived effectiveness relates positively to perceived ecoinnovations, perceived social innovations, and perceived SISC practices; (2) that perceived social innovations and SISC practices relate positively to consumer purchase intention; (3) that the effect of perceived effectiveness at a regional scale on the perception of sustainable innovations is greater than the effect of perceived effectiveness at a global scale; (4) that market sensing capability shows a positive relationship with innovation capability; (5) that these dynamic capabilities relate positively to the adoption of SISC practices; and that (6) the adoption of these SISC practices is able to improve market performance. The hypothesis that ecoinnovations were positively related to consumers' purchase intention was rejected, reflecting a gap between attitude and behavior. The testing of the hypotheses from the perspective of the consumer market and specialists, allowed the proposition of a theoretical model of sustainable innovation in supply chains oriented to the regional consumer market, based on the theory of dynamic capabilities.